Studi Deskriptif Analisa Promosi Layanan Rumah Sakit - Dewi, Ni Putu Indra; santoso, anindita; Wirawan, Handi; Tanumihardja, Joan Puspita (UI Scholars Hub, 2020)
Health services have entered an era of competition that requires hospitals to be able to provide superior services to attract consumers (patients). Hospitals need to implement an effective marketing system so that outreach targets and ultimately service utilization can be achieved by using integrated marketing communication techniques to coordinate and control various elements of the promotional mix. In this manuscript, the researcher analyzes the promotion of hospital services using a descriptive study method.